Pengaruh efisiensi modal kerja terhadap rentabilitas pada perusahaan daerah air minum (PDAM) kabupaten tana toraja tahun 2016-2020 - Pagiu, Chrismesi; Pundissing, Rati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of working capital efficiency on profitability at the Regional Water Company (PDAM) of Tana Toraja Regency in 2016-2020. The research method used is descriptive quantitative research. The data analysis technique used is simple linear regression, coefficient of determination (R2), correlation coefficient (R) and statistical t-test using the SPSS (Statistical Product and Service Solutions) application version 22. The results show that working capital efficiency has an effect positive and insignificant to the profitability of the Regional Water Company (PDAM) of Tana Toraja Regency in 2016-2020. The correlation value of 0.621 indicates a strong correlation and the coefficient of determination of 38.6% means that working capital efficiency affects profitability by 38.6% while the remaining 61.4% is influenced by other factors not examined in this study.